Comparison of endoscopic laser therapy and self expanding metal stents for palliation in patients with non-resectable oesophageal carcinoma. Issue 3 (June 2018) - Drummond, R.J.; Vass, D.G.; Robertson, K.; Sharp, C.; Gibson, S.
Abstract: Background: There are currently limited data on the comparative success of endoscopic laser therapy (NLT) and self expanding metal stents (SEMS) as palliative measures in patients with non-resectable oesophageal cancer. This study aims to assess and compare the outcomes of these methods of endoscopic palliation. Methods: Patients with non-curative oesophageal/gastro-oesophageal cancers with dysphagia were identified prospectively and consented to swallow assessment and follow-up. Patients underwent SEMS or NLT at the discretion of the treating endoscopist. Initial standardised swallow scores (0–4) were assessed. All subsequent interventions were recorded as well as survival. Results: 31 patients were recruited (30M vs 8F, mean age 70.8). There was no significant difference in age, sex or chemotherapy treatment between groups. 19(61%)patients underwent NLT as primary procedure. 20(64.5%) patients required subsequent intervention(s) (median 1, range 0–8). Primary NLT patients were more likely to require subsequent therapy (p = 0.004) and multiple procedures (p = 0.001). 8(42.1%)patients initially undergoing NLT subsequently required SEMS, while no SEMS patients underwent subsequent NLT. Swallow scores of 1 or 2 were more likely to be maintained with NLT while scores of 3 or 4 were more likely to progress to SEMS (p = 0.039). Time to repeat procedure was greater in the SEMS group (p = 0.001). Median survival was 133 days for NLT vs 60 days for SEMS (p = 0.412). Conclusion: In this series, patients selected for NLT had a trend towards longer survival, but were more likely to require repeated procedures. Those with lower early initial dysphagia scores were more likely to be maintained by NLT alone.